INCREASING NUMBER OF JAPANESE INTERNSHIP SELECTION GRADUATES - Kardinasari, Youlia (Efficient: Indonesian Journal of Development Economics, 2019)
The internship program to Japan is expected to be able to reduce unemployment due to missmatch between the type and quality of labor produced by the world of education towards the workforce needs in the industrial world. However, the number of graduates of the selection of apprenticeship programs to Japan through government channels is still low, which is below 30% compared to private channels whose graduation rates can reach 95%. The purpose of this study was to analyze and determine the internal factors and eksternal factors of internship program to Japan and to analyze and find out the strategies that must be done by the government to increase the number of graduates of the selection. This study uses primary and secondary data with descriptive analysis method and SWOT analysis. The results of this study indicate that the internal factor of strength is a particular government program. The weakness of the program is the lack of socialization. eksternal factor Opportunities in the internship program to Japan are to get business capital after an internship to prepare a business. The biggest threat is that selection costs are still quite high. The strategy that can be done to increase the number of graduates of the selection of apprenticeship programs to Japan through government pathway in Central Java is with an aggressive strategy. Program magang ke Jepang diharapkan dapat mengurangi pengangguran karena adanya ketidaksesuaian antara jenis dan kualitas tenaga kerja yang dihasilkan oleh dunia pendidikan terhadap kebutuhan tenaga kerja di dunia industri. Namun, jumlah lulusan yang memilih program pemagangan ke Jepang melalui saluran pemerintah masih rendah, yaitu di bawah 30% dibandingkan dengan saluran swasta yang tingkat kelulusannya bisa mencapai 95%. Tujuan dari penelitian ini adalah untuk menganalisis dan menentukan faktor internal dan faktor eksternal dari program magang ke Jepang dan untuk menganalisis dan mengetahui strategi yang harus dilakukan oleh pemerintah untuk meningkatkan jumlah lulusan seleksi. Penelitian ini menggunakan data primer dan sekunder dengan metode analisis deskriptif dan analisis SWOT. Hasil penelitian ini menunjukkan bahwa faktor kekuatan internal adalah program pemerintah tertentu. Kelemahan program adalah kurangnya sosialisasi. faktor eksternal Peluang dalam program magang ke Jepang adalah untuk mendapatkan modal bisnis setelah magang untuk mempersiapkan bisnis. Ancaman terbesar adalah biaya seleksi masih cukup tinggi. Strategi yang dapat dilakukan untuk menambah jumlah lulusan dalam pemilihan program magang ke Jepang melalui jalur pemerintah di Jawa Tengah adalah dengan strategi yang agresif.